O Kształtowaniu Kratownic na Minimum Potencjału - Bierniawski, A.; Grochowski, B. (Engineering Transactions, 1960)
The paper a contains a tentative solution of the problem of design of a system with three loaded models, giving the conditions of rationality of introducing the fourth unloaded node and fixing the position of this node by designing the four-node structure for minimum potential. The paper is based on the following theorem previously established by the Strength Design Groups of the ZMOC, IPPT, under the direction of Prof. Zbigniew WASIUTYŃSKI. (1) The theorem on the equivalence of the design for minimum potential and the same volume of lattice with the minimum material design for a given potential. (2) The theorem on the equivalence of the minimum potential design with the design for uniform normal stresses.